Yield and quality of net melon cultivated in sand in the greenhouse - De Gusmao, Monica T.A.; Factor, Thiago L. [UNESP]; De Gusmao, Sergio A.L.; De Araújo, Jairo A.C. [UNESP]; Baracioli, Fernando Zanovelli [UNESP] (My University, 2003)
The behavior of two hybrids of muskmelon ('Bônus no 2' and 'Don Carlos') in relation to the productivity and quality of its fruits, making use of fertigation in sand substrate in protected environment, was studied. Amianthus cement structures of the Canalete runlet type were used to keep the plants 0.30m from each other and 1.0m between lines. 'Don Carlos' hybrid had fruit mean weight, longitudinal and transversal diameter, pulp mean thickness, and total acidity substantially superior in relation to 'Bônus no 2'. Considering the total soluble solid content, 'Bônus no 2' had better results. However, there was no significant difference in fruits/plant or pulp thickness between the two hybrids.
Keywords: Cucumis melo l.; Cucurbitaceae; Greenhouse; Productivity; Quality; Substrate